Tala sangraha compendium of talas in Karnatak music - Sundaram, B. M. (Bangalore Percussive Arts Centre, 1987)
Beat indications and their variations with notation.
Keywords: Tala -- Dictionaries; Music -- India -- Dictionaries; Music, Karnatic -- Dictionaries